Different Culture Means Different Discourse Perception: Personal True-based Story in Light of Face-Threatening Acts - Almoayidi, Khedir (International Journal of Language and Literary Studies, 2024)
One of the driving motives of language use is to pave the way for communication and understanding. However, sometimes the exclusive use of language cannot help to stream mutual understanding among people who have different cultures which, unfortunately, researchers have not treated in much detail. As such, this study brings to light the essential role of cultural norms and conventions in interaction. Based on a true story, the current study shows that different cultural norms can raise issues that cause misunderstanding and could lead to face threatening acts. This manifests that being aware of the interaction conventions of one’s culture does not necessarily mean that speakers of other cultures will have the same conventions, and what speakers of a certain culture consider to be polite may be considered impolite and trespassing in other cultures.